The complete mitochondrial genome of Tetragonia tetragonioides (Pall.) Kuntze and its phylogenetic implications. Issue 9 (2nd September 2021) - Hu, Shunxin; Liu, Jingxi; Chen, Lizhu; Chen, Wei; Li, Yanxiang; Gao, Jiqing; Fu, Rao; Sun, Chunxiao; Li, Bin; Tang, Junwei; Qiao, Peng; Li, Meng; et al.
Abstract: The complete mitochondrial genome sequence of Tetragonia tetragonioides (Pall.) Kuntze was assembled and characterized in the present study. The mitochondrial genome was 347, 227 bp in length and had a GC content of 43.84%, including 24 transfer RNA (tRNA) genes and three ribosomal RNA (rRNA) genes. Phylogenetic analysis showed that T. tetragonioides was close to and Sesuvium portulacastrum .